DIGITAL TECHNOLOGY IN COMPANIES AND ITS IMPORTANCE IN EDUCATING PEOPLE - José Raimundo, Anderson; do Carmo Rodrigues, José (Journal of Interdisciplinary Debates, 2023)
The objective of this work is to show how technology is important in educating people at work and how qualification or training can influence performance and productivity in companies. The purpose of the course completion work is to show the difficulties encountered by many workers from various sectors in adapting to the system (work with computers), to show what companies do to remedy this problem and to propose solutions according to the technology currently used. . When analyzing the situations of companies that use an ERP integrated management system, many situations were encountered in which most users are used to technology, that is, many of them do not have adequate experience or knowledge to use systems according to their function. . In addition, the company itself does not prepare newcomers and/or employees with a long time in the company to adapt according to the technology used by them. Some solutions were found to solve the problems, such as the availability of online and printed manuals. In addition, another factor that contributed to the education of users were workshops and practical training. After this period, surveys were carried out on post-training performance and most people claim that performance at work improved significantly, generating great results.